No clue about bioplastics - Erik Ansink; Louise Wijk; Frederiek Zuidmeer (Tinbergen Institute, 2019)
We analyze recycling decisions for bioplastics using a natural field experiment. The potential environmental benefits of these new plastics may not materialize if they are recycled incorrectly. The field experiment that we set up to test this recycling behavior exploits the setting of a lemonade tasting. In our experimental treatments, subjects are exposed to different types of bioplastics logos on their cups as well as varying amounts of recycling information. We use two types of bioplastics and compare these to conventional plastics in terms of whether subjects recycle the cups correctly. Our results show that over 90% of subjects dispose of their cup with plastic waste and that none of our treatments can snap subjects out of this default behavior. We interpret this finding as subjects having no clue how to recycle bioplastics. More generelly, these results point to skepticism regarding new products or varieties whose environmental benefits depend on proper use or disposal.
Keywords: Q53; C93; 330; Recycling; field experiment; bioplastics